Modelling and computational analysis of heat-transfer in multi-geometry and multi-phase flow of Newtonian and non-Newtonian fluids in pipes and channels - Mavi, Anele (Department of Mathematics and Applied Mathematics, 2023)
The thesis develops and computationally analyzes mathematical models for multi-geometry heat exchanger design and for multi-phase flow problems involving boiling and bubble formation. Newtonian fluids, Newtonian-Fluid-Based- Nanofluids, and non-Newtonian fluids are all considered in the thesis. The Newtonian-Fluid-Based Nanofluids (NFBN) are designed from the homogeneous mixing of a Newtonian base-fluid with solid nano-particles. Water will be used as the Newtonian base-liquid and two types of nano-particles will be considered, aluminium oxide (Al2O3) and titanium oxide (TiO2) nano particles. The non-Newtonian fluids in this thesis are modelled via the Giesekus viscoelastic constitutive equations. For the multi-geometry heat-exchanger problems, the thesis will focus attention on counterflow heat exchangers in cylindrical geometries, specifically counterflow, double-cylinder heat-exchangers. The problem statement in this direction focuses on the non-isothermal dynamics and heat-transfer characteristics for a counterflow, double-cylinder heat-exchanger design with a viscoelastic fluid flowing in the core (inner) cylinder and a Newtonian fluid flowing (in the opposite direction) in the shell (outer annulus) region. Investigations are extended to investigate the effects of using Newtonian-Fluid-Based Nanofluids (NFBN) instead of ordinary newtonian fluids in the outer annulus. The Giesekus viscoelastic constitutive model is used to model and describe the rheological behaviour of the viscoelastic core-fluid. The numerical algorithms for these problems are based on the Finite Volume Methods (FVM) implemented on the OpenFOAM software. The numerical instabilities due to the High Weissenburg Number Problem (HWNP) are resolved by employing either the Discrete Elastic Viscous Stress Splitting (DEVSS) or the Log Conformation Reformulation (LCR) techniques. The pressure-velocity coupling is resolved via the Pressure Implicit with Splitting of Operator (PISO) approach. The results illustrate that the use of NFBN as the coolant fluid leads to enhanced cooling of the hot core-fluid as compared to using an ordinary (nano-particle free) Newtonian coolant. Specifically, the results illustrate that an increase in the nano-particle volume-fraction, in the coolant shell fluid, leads to enhanced heat exchange characteristics from the hot core-fluid to the coolant shell-fluid. The multi-phase flow investigations focus on the simulation of three-phase (solid-liquid-gas) boiling flow and bubble formation problems in rectangular channels. The numerical algorithms are also based on the Finite Volume Methods (FVM) implemented on the OpenFOAM software. The numerical algorithms additionally implement both the volume-of-fluid (VOF) methods for liquid-gas interface tracking as well as the volume-fraction methods to account for the concentration of embedded solid nano-particles in the liquid phase. Water is used as the base-liquid and the solid phase is modelled via metallic nano particles, both aluminium oxide (Al2O3) and titanium oxide (TiO2) nano-particles are considered. The (aluminium oxide or titanium oxide) nano-particles are homogeneously mixed within the water base liquid. The gas phase is considered as a vapour arising from the boiling processes of the liquid-phase. In addition to the FVM and VOF numerical methodologies for the discretization of the governing equations, the pressure-velocity coupling is resolved via the PIMPLE algorithm, a combination of the Pressure Implicit with Splitting of Operator (PISO) and the Semi-Implicit Method for Pressure-Linked Equations (SIMPLE) algorithms. The simulations and results accurately capture the formation of vapour bubbles in the two-phase (particle-free) liquid-gas flow and additionally the computational algorithms are similarly demonstrated to accurately illustrate and capture simulated boiling processes. The presence of the nano-particles is again demonstrated to enhance the heat-transfer, boiling, and bubble formation processes.